Casting a Long Shadow: How Parental Risky Behaviors Impair Child Development in Russia - Lucia Mangiavacchi; Luca Piccoli; Steven Stillman (Institute of Labor Economics (IZA), 2025)
This paper estimates the short-run impact of parental risky behaviors on multiple dimensions of child development using 30 years of data from a representative Russian longitudinal survey. We use factor analysis to construct a composite index of parental risky behaviors and health habits. The panel nature of the data allows us to implement individual and household fixed-effects models, which control for all time-invariant unobserved heterogeneity that might correlate with both parenting and child outcomes. We find that exposure to parental risky behaviors adversely affects children's educational attainment (grade-for-age) and increases their propensity for risky behaviors, specifically smoking and drinking. Conversely, we find no significant impact on soft skills and only weak evidence of negative health outcomes. These impacts are more pronounced for older children and those in higher-income households.
Keywords: D1; I1; I2; I3; 330; risky behaviors; child development; intergenerational transmission; parental role model